Rekonstruksi Fiqhu al-Bi’ah untuk Keberlanjutan Energi Terbarukan di Tengah Krisis Energi Global - Andi Rezal Juhari; Muhammad Suhufi; Misbahuddin M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The global energy crisis, characterized by high dependence on fossil fuels, has created not only a challenge of availability but also a threat to sustainability. Islam views this issue within the framework of humans as khalÄ«fah fi al-ard, who are entrusted with the responsibility to manage and preserve the earth. This study aims to reconstruct Islamic law, particularly fiqh al-biâ€™ah, as a normative and ethical foundation for renewable energy development in the face of climate change and resource depletion. Using a normative qualitative method with approaches of ushul fiqh, maqÄá¹£id al-sharÄ«â€˜ah, and contemporary analysis, the research draws from primary sources such as the Qurâ€™an, Hadith, fatwa, and international energy reports, as well as supporting literature. The findings reveal that the continued use of fossil energy aligns with the concepts of isrÄf (wastefulness) and ifsÄd fi al-ard (corruption on earth), thus contradicting the ethical principles of Islam. Meanwhile, renewable energy represents a manifestation of maslahah (public benefit), â€˜adl (justice across generations), and amanah (trust), which are fundamental Islamic values. The study concludes that reconstructing Islamic law through maqÄá¹£id and legal maxims such as lÄ á¸arara wa lÄ á¸irÄr provides a solid theological and ethical basis to support the transition from fossil fuels to renewable energy. This reconstruction can be applied at individual, institutional, and policy levels, ensuring that the transition is not only technically feasible but also aligned with Islamic principles of sustainability.